AN EXPERIMENTAL FACILITY FOR INVESTIGATING HYDROMAGMATIC ERUPTIONS AT HIGH-PRESSURE AND HIGH-TEMPERATURE WITH APPLICATION TO THE IMPORTANCE OF MAGMA POROSITY FOR MAGMA-WATER INTERACTION - Trigila R.; Battaglia M.; Manga M. (My University, 2007)
An experimental facility has been developed to investigate magma-water interaction (MWI). The facility operates in a high-pressure and high-temperature environment, with temperatures up to 1,200°C and pressures up to 200 MPa. Cylindrical sample-holders (20 by 180 mm in size) are heated conductively to yield a three phase (melt, crystals and gas) system, and then water (or other fluid) is injected into the sample through a capillary tube (diameter 0.5 mm, length ca. 1,000 mm) under controlled conditions. Pressure, volume and temperature changes are continuously recorded during every phase of the experiments. To test this facility, MWI is studied at subliquidus temperatures (800 and 900°C) and pressure (8 MPa), using a leucite tephrite sample with two different initial grain sizes. Because of the grain-size dependence of sintering, the two starting materials produce magmas with different textures at the same temperature: porous magma for large initial grain sizes and dense magma for small initial grain sizes. In these experiments 1.5 g of water at room temperature is injected into 6.0 g of partially molten sample at velocities ranging from 1 to 3 m/s. We find that the extent of fragmentation and transport caused by MWI are mainly controlled by the texture of the interacting sample with explosive interaction occurring only for porous magmas.
Keywords: EXPERIMENTAL VOLCANOLOGY; HYDROMAGMATISM; MAGMA-WATER INTERACTION; VOLCANIC MFCI; HPHT FACILITY; LATERA VOLCANO; SPATTER FLOW